1996
DOI: 10.1002/(sici)1096-9896(199607)179:3<294::aid-path590>3.3.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in Human Monocyte‐macrophages Exposed to Oxidized Low Density Lipoprotein

Abstract: This study has demonstrated the toxicity to human monocyte-macrophages of low-density lipoprotein (LDL) which had been artificially oxidized using copper sulphate. The assays of cell damage used were tritiated adenine release, neutral red staining, lactate dehydrogenase leakage, and MTT dye reduction. Toxicity was concentration- and time-dependent. Exposure to native LDL under the same conditions did not result in toxicity. Transmission electron microscopy of cells exposed to oxidized LDL showed characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
0
14
1
Order By: Relevance
“…Increasing numbers of reports indicate that Ox-LDL is cytotoxic to macrophages and contributes to macrophage apoptosis [31][32][33], which may relate to downregulating expression of the anti-apoptotic genes Bcl-2 and up-regulating the pro-apoptotic genes Bax and Caspases [34][35][36][37]. However, in the present study, the apoptotic index, including morphology, DNA ladder, and the quantity of apoptotic and necrotic cells, in groups treated with or without Ox-LDL were not obviously different.…”
Section: Discussioncontrasting
confidence: 78%
“…Increasing numbers of reports indicate that Ox-LDL is cytotoxic to macrophages and contributes to macrophage apoptosis [31][32][33], which may relate to downregulating expression of the anti-apoptotic genes Bcl-2 and up-regulating the pro-apoptotic genes Bax and Caspases [34][35][36][37]. However, in the present study, the apoptotic index, including morphology, DNA ladder, and the quantity of apoptotic and necrotic cells, in groups treated with or without Ox-LDL were not obviously different.…”
Section: Discussioncontrasting
confidence: 78%
“…One thousand cells were indexed for each exposure (control, 5 and 20 mg/mL), and the entire experimental process repeated four times for statistical analysis. Cells were determined as either apoptotic (shrunken, vacuoles in a condensed cytoplasm, heavily capped chromatin), necrotic (electron-lucent with cytoplasmic and nuclear contents appearing leached out) or healthy by comparing cell morphology to reference images from previous studies [31].…”
Section: Temmentioning
confidence: 99%
“…Thus, oxLDL levels show a significant positive correlation with the severity of acute coronary syndromes such as myocardial infarction (MI) and unstable angina, and the more severe lesions contain a significantly higher percentage of oxLDLpositive macrophages [8]. According to this scenario, it has been shown that oxLDL is cytotoxic to cultured cells and induces apoptosis and necrosis of vascular endothelial cells, smooth muscle cells (SMCs), and macrophages [9][10][11][12]. These processes have been proposed to lead to plaque vulnerability and potential rupture, which is ultimately responsible for acute atherothrombotic vascular occlusion and tissue infarction.…”
Section: Introductionmentioning
confidence: 99%